Gadaa: An Indigenous Democracy of Oromo people on Promoting Gender Equality, Guji Oromo in focus, Oromiya - Gemechu Kenea Geleta (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This paper deals the role Gadaa system in balancing the power of women and men. The aim of this paper is to show the role of women in Gadaa system including the role in ritual, power transfer and other social-cultural activities of Guji people. The study employed qualitative research approach with exploratory research design, because of the nature of the identified research problem. Purposive sampling was employed and the relevant respondents from the target group were selected carefully by the researcher and document was reviewed to get reliable and rich data. The paper come up with the idea that, even though the role of women in the Gadaa political power has been created controversies among scholars Gadaa system strongly allowed the women to participate in the social, cultural, economic and political issue. This paper argued that Gadaa system is unprecedented indigenous democracy in which the rights of women and female are respected. Gadaa system has great role in protecting the right of women, enforced a gender-based division of labor in Oromo society. Under this system husband and wife are obliged to use their properties equally. The instrument and institution through which women's rights are duly respected is known as Siinqee - which is a procedure in which women organize themselves in group to stand up for their rights